Digestive alterations and nutritional recommendations in low birth weight piglets - Quisirumbay Gaibor, Jimmy Rolando (2019)
The intense genetic selection carried out in sows in the last decades has generated a hyperprolific sow with greater litter sizes and a greater proportion of piglets with weight lower than 1 kg, called low birth weight piglets (LBWP). The LWBP suffer from gastrointestinal morphophysiological alterations, which generates a lower digestive capacity in order to efficiently take advantage of the nutrients of the diet, affecting their productive performance and survival. This has triggered a series of research to find nutritional and feeding alternatives that allow this type of piglets to achieve better productive parameters. The objective of this document was to gather information about the most important digestive alterations in LBWP and the nutritional options to improve their survival and productive performance.